The Effect of the G20 Summit in Bali on Creative Economy and Tourism: Economic Impact Analysis of High-Level Events - Khairune Nisa, An Nuur (Jurnal Toursci, 2023)
This research examines the impact of the G20 Summit in Indonesia in 2022 on the country's economy, especially in the creative economy and tourism sectors. The G20 summit in Bali became a platform for multilateral collaboration between 19 major economies and the European Union. The main focus of the conference is on issues of global economy and sustainable development with the theme "Recover Together, Recover Stronger." This research method involves the analysis of economic and statistical data, including official statements from Finance Minister Sri Mulyani Indrawati and the Central Statistics Agency (BPS). This data includes the impact on domestic consumption, Gross Domestic Product (GDP) growth, and Micro, Small and Medium Enterprises (MSMEs) sector growth. In addition, the research involved an analysis of women's empowerment programs in MSMEs, fund allocation, and the level of realization of the Kredit Usaha Rakyat (KUR) program. The research includes an analysis of the positive effects on infrastructure in Bali and the improvement of tourism image. Data on the influence on the tourism sector includes statistics on foreign tourist visits, hotel occupancy, and an increase in tourist visits during the conference period. The study also includes analysis from the MSMEs, restaurants, arts and crafts, and transportation sectors to detail the economic impact in various sectors.